Identification of Volatile Compounds in Soy Milk Drinks Using Solid Phase Microextraction-Gas Chromatography-Mass Spectrometry (SPME-GC-MS) - Sari, Aisah Kensar Nawang Wulan; Hanwar, Dedi (Syntax Literate, 2024)
The distinctive aroma produced by soy milk is thought to come from volatile compounds. The development and use of soy milk derivative products require a deep understanding and characterization of the flavor profile. The aim of this study was to identify volatile flavoring compounds found in soy milk made from imported and local soybeans. Milk samples extracted using the headspace-SPME method at a temperature of 60°C for 20 minutes, and analyzed using GC-MS. The results obtained, detected as many as 23 major volatile compounds (relative levels> 1%) in both samples. The difference in total volatiles produced between the two samples showed that there was a significant difference (P <0.05), while the difference in relative levels between compounds that often appear such as pentanal in both samples showed insignificant results (P> 0.05). It can be concluded that the origin of soybeans between imported and local soy milk influences the total amount of volatile compounds identified, however, it does not significantly influence the flavour and aroma characteristics caused by the pentanal compound.